Skin temperature and heart rate rhythms in infants of extreme prematurity. Issue 7 (July 1992) - D'Souza, S W; Tenreiro, S; Minors, D; Chiswick, M L; Sims, D G; Waterhouse, J
Abstract : Nine preterm infants of 26 to 29 weeks' gestational age and 792 to 1200 g birth weight spent six to 17 weeks in our neonatal medical unit. Hourly recordings of skin temperature and heart rate were carried out. The first five to 15 weeks were spent in the intensive care ward, in continuous light, due to various medical conditions. After recovery they were moved to a nursery for one to nine weeks, with 12 hourly periods of light and darkness. Four infants developed circadian rhythms in temperature and three in heart rate in light-dark periods, the remainder failing to do so. Some infants take longer than others to develop circadian rhythms but the reasons for this are not clear. It is suggested that earlier exposure to a light-dark environment may synchronize the 'body clock' to a 24 hour period in more preterm infants.